Stupeni . Stupeni . Steps . Ступени - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by the state television (Moscow) in the USSR and recorded by the Radio Liberty Monitoring Unit in Munich as part of their effort to track and analyze the official media of the republics of the Soviet Union. Передача государственного телевидения (Москва, СССР) была записана отделом мониторинга радиостанции Свобода (Мюнхен) как часть проекта по анализу официальных средств информации республик Советского Союза. The program explores the problems of boarding schools in the USSR: interviews with the ex-director, students and staff of one of the schools. Contributors: Ardanov, Khizur (Director); Vereshchagin, Andrei (Director) Фильм о специальных интернатах в СССР. Интервью с воспитанниками, воспитателями и бывшей руководительницей интерната. Создатели: Арданов, Хизур (Режиссер); Верещагин, Андрей (Режиссер)